Age As Moderator of Emotional Stroop Task Performance in Posttraumatic Stress Disorder (PTSD) - Bielecki, Maksymilian; Popiel, Agnieszka; Zawadzki, Bogdan; Sedek, Grzegorz (Frontiers in Psychology, 2017)
Emotional Stroop Task (EST) has been extensively used to investigate attentional processes in posttraumatic stress disorder (PTSD). Even though ageing significantly changes the dynamics of emotion-cognition interactions, very little is known about its role in shaping EST performance in PTSD patients. In the present study we tested a uniquely large sample of motor vehicle accident victims. Data of 194 participants (75.3% female; mean age = 36.64 years, SD = 12.3) were included in the analysis, out of which 136 (70.1%) were diagnosed with PTSD. Prior to the psychiatric assessment, participants completed the pictorial version of EST (neutral, positive, negative, and accidents photos were presented). Comparison of the PTSD and control groups revealed a specific increase in reaction times related to the exposure of trauma-related material. At the same time, previously unreported, moderating effects of age were also discovered. Older participants, in contrast to the younger group, showed no increase in reaction times and interference scores in trials where accident photos were presented. Our study points to the key role of age as a previously understudied factor modifying EST performance in PTSD patients.